Analysis of the Concept of the Attribute of Tawab and Social Interaction: صفت التوَّابُ کے مفہوم کا تجزیہ اور سماجی تفاعل - Khan , Dr. Usman; Farhadullah , Dr. (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
The attribute of Tawab (The Accepter of Repentance) is among the most valuable trat of Allah (SWT). It is mentioned in Quran and hadith in various contexts, and it has a profound impact on human psychology and behavior. This paper analyzes the concept and function of Tawab according to the Quran and hadith. It begins by discussing the meaning of Tawab and its scope of action. The paper then examines the application of this attribute in hadith of Prophet Muhammad (peace be upon him) and the meanings and concepts given by lexicographers and scholars. The paper further explores the relationship between this attribute and the relationship between humans, as well as the social implications of this attribute. It argues that the attribute of Tawab is not only a purely divine right but a social value. It is reflected in humans as a social value and encompasses the entire system of the world. Every individual, society, nation, and people who strive for peace and security in society must have this value in general. The paper finally concludes by highlighting the importance of the attribute of Tawab in human life. It argues that this attribute can help humans to overcome their mistakes and sins, and to lead a more fulfilling and righteous life.